European Association of Urology Guidelines on Upper Urinary Tract Urothelial Cell Carcinoma: 2015 Update - Rouprêt, Morgan; Babjuk, Marko; Compérat, Eva; Zigeuner, Richard; Sylvester, Richard J; Burger, Maximilian; Cowan, Nigel C; Böhle, Andreas; Van Rhijn, Bas W G; Kaasinen, Eero; Palou, Joan; Shariat, Shahrokh F (European urology, 2015)
CONTEXT: The European Association of Urology (EAU) guidelines panel on upper urinary tract urothelial cell carcinoma (UTUC) has prepared updated guidelines to aid clinicians in the current evidence-based management of UTUC and to incorporate recommendations into clinical practice. OBJECTIVE: To provide a brief overview of the EAU guidelines on UTUC as an aid to clinicians. EVIDENCE ACQUISITION: The recommendations provided in the current guidelines are based on a thorough review of available UTUC guidelines and articles identified following a systematic search of Medline. Data on urothelial malignancies and UTUC were searched using these keywords: urinary tract cancer; urothelial carcinomas; upper urinary tract, carcinoma; renal pelvis; ureter; bladder cancer; chemotherapy; nephroureterectomy; adjuvant treatment; instillation; neoadjuvant treatment; recurrence; risk factors; and survival. References were weighted by a panel of experts. EVIDENCE SYNTHESIS: Due to the rarity of UTUC, there are insufficient data to provide strong recommendations (ie, grade A). However, the results of recent multicentre studies are now available, and there is a growing interest in UTUC. The 2009 TNM classification is recommended. Recommendations are given for diagnosis and risk stratification as well as radical and conservative treatment, and prognostic factors are discussed. A single postoperative dose of intravesical mitomycin after nephroureterectomy reduces the risk of bladder tumour recurrence. Recommendations are also provided for patient follow-up after different therapeutic strategies. CONCLUSIONS: These guidelines contain information on the management of individual patients according to a current standardised approach. Urologists should take into account the specific clinical characteristics of each patient when determining the optimal treatment regimen, based on the proposed risk stratification of these tumours. PATIENT SUMMARY: Urothelial carcinoma of the upper urinary tract is rare, but because 60% of these tumours are invasive at diagnosis, an appropriate diagnosis is most important. A number of known risk factors exist.
Keywords: nádory ledvin; Ureter; Humans; Administration, Intravesical; ureter; aplikace intravezikální; karcinom z přechodných buněk; Chemotherapy, Adjuvant; ureteroskopie; Urothelial carcinoma; Kidney Pelvis; Survival; lidé; společnosti lékařské; Urinary tract cancer; adjuvantní chemoterapie; ledvinná pánvička; Ureteroscopy; Guidelines; Cytology; Ureteral Neoplasms; nádory močového měchýře; Risk factors; Carcinoma, Transitional Cell; urologie; mitomycin; Renal pelvis; Mitomycin; Societies, Medical; lokální recidiva nádoru; nádory močovodu; Nephrectomy; nefrektomie; Urinary Bladder Neoplasms; Urology; Neoplasm Recurrence, Local; Kidney Neoplasms; Antibiotics, Antineoplastic; Nephroureterectomy; protinádorová antibiotika